OWLS-LO: extending OWL-S to support learning object. (2016) - Mahmoud, Chaker Ben; Bettahar, Fathia; Azaiez, Ikbel; Gargouri, Faiez
The essential challenge in e-learning is finding and identifying a learning object from a big corpus on the one hand, and ensuring the independence and reusability of learning objects in a different context, on the other hand. These problems can be solved by using the principles of Web service paradigm. In this paper, we propose a semantic description of learning services that encompasses the description of the learning intention and the use of context that characterise a learning object. Then, we propose a semantic service descriptor, based on our OWL-S extension, to enrich service registry. The feasibility of our extended semantic OWLS-LO is proved by experimental results obtained.